The impact of dietary supplementation with astaxanthin on egg quality in Atlantic cod broodstock (Gadus morhua, L.) - Sawanboonchun, Jarin; Roy, William; Robertson, Derek; Bell, J Gordon (Aquaculture, 2008)
This study investigated the effect on egg quality of dietary supplementation of Atlantic cod broodstock with the carotenoid astaxanthin (ASTA). Duplicate groups of farm-reared Atlantic cod broodstock were fed either a control diet with no added ASTA, or an ASTA supplemented diet (73.7 mg/kg dry weight; Carophyll Pink®) for 2 months prior to peak spawning. The results indicated that ASTA uptake into eggs from the broodstock diet was highly efficient. Fish fed the diet supplemented with ASTA produced fewer batches of eggs, but the mean number per batch of eggs spawned/kg female was higher, and numbers of floating eggs and numbers of fertilised eggs per kg female in each batch were also significantly improved. A correlation between the egg ASTA content and fertilisation success of individual batches was identified. This improvement in egg quality demonstrated the potential value of ASTA supplementation of broodstock diets for cod. ASTA supplementation produced a 20% increase in the number of eggs per batch spawned, a 37% increase in the number per batch of floating eggs per kg female and a 47% increase in the number per batch of fertilised eggs per kg female. These results clearly demonstrate significant benefits of ASTA supplementation of cod broodstock feeds in terms of improved egg quality and larval production.